2008
DOI: 10.1093/wjaf/23.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Nonhost Angiosperm Volatiles and Verbenone Protect Individual Ponderosa Pines from Attack by Western Pine Beetle and Red Turpentine Beetle (Coleoptera: Curculionidae, Scolytinae)

Abstract: Nonhost angiosperm volatiles (NAV) and verbenone were tested for their ability to protect individual ponderosa pines, Pinus ponderosa Dougl. ex. Laws., from attack by western pine beetle (WPB), Dendroctonus brevicomis LeConte, and red turpentine beetle (RTB), Dendroctonus valens LeConte (Coleoptera: Curculionidae, Scolytinae). A combination of (−)-verbenone and eight NAVs [benzyl alcohol, benzaldehyde, guaiacol, nonanal, salicylaldehyde, (E)-2-hexenal, (E)-2-hexen-1-ol, and (Z)-2-hexen-1-ol] (NAVV) significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…A ninecomponent blend [benzyl alcohol, benzaldehyde, guaiacol, nonanal, salicylaldehyde, (E)-2-hexenal, (E)-2-hexen-1-ol, (Z)-2-hexen-1-ol and (-)-verbenone] reduced trap catch by 87% compared to the attractantbaited control [31]. Based on this work, Fettig et al [32] were first to demonstrate the successful application of a semiochemical-based tool for protecting P. ponderosa from mortality attributed to D. brevicomis. Additional research confirmed the effect [33], but initial blends were complex and likely not feasible for operational use.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…A ninecomponent blend [benzyl alcohol, benzaldehyde, guaiacol, nonanal, salicylaldehyde, (E)-2-hexenal, (E)-2-hexen-1-ol, (Z)-2-hexen-1-ol and (-)-verbenone] reduced trap catch by 87% compared to the attractantbaited control [31]. Based on this work, Fettig et al [32] were first to demonstrate the successful application of a semiochemical-based tool for protecting P. ponderosa from mortality attributed to D. brevicomis. Additional research confirmed the effect [33], but initial blends were complex and likely not feasible for operational use.…”
Section: Introductionmentioning
confidence: 59%
“…In that experiment, 4.9 ± 1.5 and 0.2 ± 0.1 D. ponderosae (mean ± SEM, n = 42) were captured in the control and Verbenone Plus treatments, respectively. Several years of research initially resulted in the development of Verbenone Plus for protecting P. ponderosa from mortality attributed to D. brevicomis [27][28][29][31][32][33][34], where it serves as the only effective semiochemical-based tool for tree protection in that system [28].…”
Section: Discussionmentioning
confidence: 99%
“…Verbenone pouches (along with NHVs) (Fettig et al 2005(Fettig et al , 2008a(Fettig et al , 2008b and verbenone flakes (Gillette et al 2006) have been shown to provide significant protection of individual pines from attack by RTB. The application of verbenone-releasing flakes at the rate of 3.57 oz (15 g) of flakes/tree reduced attack rate by RTB on individual trees to nearly zero compared to control trees (Gillette et al 2006), so this method gives very good individual tree protection.…”
Section: Pushmentioning
confidence: 99%
“…Although verbenone showed some early promise as an anti-attractant for WPB (Bedard et al 1980, Tilden et al 1985, when used alone for tree protection its efficacy has been equivocal (Bedard and Wood 1981, Gillette et al 2009a, 2009b. More recently, Erbilgin et al (2007bErbilgin et al ( , 2008 and Fettig et al (2005Fettig et al ( , 2008aFettig et al ( , 2008b have demonstrated efficacy of adjuvants to verbenone and other active ingredients to enhance efficacy of a "push" or "push-pull" technique for WPB. The adjuvants (NHVs), which are largely those that have shown efficacy for MPB, are still being tested for areawide use but have shown substantial efficacy in individual tree tests (Fettig et al 2008a(Fettig et al , 2008b.…”
Section: Western Pine Beetle (Wpb)mentioning
confidence: 99%
“…Many field investigations have lead to the use of some of the anti‐aggregation pheromones and plant‐produced compounds, such as green leaf volatiles, for preventing or minimizing economic damage caused by bark beetles (Dickens et al , 1992; Zhang & Schlyter, 2004). Most research with anti‐aggregation pheromones for bark beetles has focused on verbenone (Amman, 1994; Borden, 1996), but more recent papers report use of verbenone in combination with other potential semiochemicals, such as nonhost volatiles (Fettig et al , 2005, 2008). These studies have demonstrated a reduction in the attraction of beetles, but only by adding a large number of additional chemicals; such multi‐component blends may be prohibitively expensive to register for operational use.…”
Section: Introductionmentioning
confidence: 99%